Social media usage and effect studies in Malaysian journals and PhD dissertations from 2004-2015 - A Rahman, Nur Atikah (2018)
The development of social media plays a phenomenal role in Malaysia, garnering more research on the usage and impact of social media on the users. This illustrates the interest on this phenomenon is immensely growing. Despite the rising amount, previous efforts in exploring the state of social media studies in Malaysia is scarce compared to the West. In keeping pace with the progression of social media, literature on social media in Malaysia were examined for a more comprehensive outlook on the research patterns of the field from the years 2004 until 2015. Specifically, this research utilised quantitative content analysis and in-depth interviews. Two content analyses were conducted on 79 articles in selected Malaysian academic journals and 12 doctoral theses from universities in Malaysia that had conducted social media studies. Descriptive statistics were used to identify the research patterns by adopting a framework of analysis from past literature including: theoretical application, research topic, methodological approach, social media type and development phases of social media research. In-depth interviews of six mass communication and social media scholars in Malaysia were also conducted. The interviews were conducted through an open-ended set of interview protocols to explore their perceptions on the trends of communication theories in social media studies. The interviews were analysed using thematic analysis. The results indicated that social media research in Malaysia was still in formative stage as this communication technology is considered new and Malaysian scholars still lack of skills and experiences in understanding the field. However, a pattern of increase was apparent on the numbers of social media studies. Moreover, the theoretical presence in social media research in Malaysia is relatively higher than the theoretical footings in the West. The most prevalent communication theories were uses and gratifications, agenda-setting and diffusion of innovations. Scholars emphasised cited theories were chosen based on the research background, personal connection and relevancy to the social media issue. Most theories were applied as theoretical framework, followed by merely referencing and comparison of theories. Although theoretical application in social media studies showed an upward trend, the practice of construction and expansion of theories among Malaysian scholars is still limited, implicating a need for a more solidified and elaborated theoretical foundation. The findings showed that theoretical footing were underdeveloped because existing theories were considered more relevant for their research, lack of credible scholars, no affiliation amongst scholars and incompetency in English. Several factors were suggested in generating theories such as acquiring solid theoretical foundation, a call for more teamwork among scholars, improvement of facilities in institutions, upgrading of communication programmes in universities and enhancement of quality in journals. This study recognised the need for more research topics on the improvement and creation of new concepts and theories for social media; better methodological rigours and wider dispersion on the type of social media. The study concludes with main issues of theoretical development and recommends further fundamental research for the creation of theories to understand the usage and effect of social media on local culture and values of Malaysian users.